THE IMPORTANCE OF PRESERVING INDIGENOUS LANGUAGES - Muradulloyeva Sevinch Soxibjon qizi (TALABALAR ILMIY KONFERENSIYASI "TILSHUNOSLIK MASALALARI – YOSH TADQIQOTCHILAR NIGOHIDA", 2025)
The topic explores the crucial role of languages, collectively known as body language, in conveying and interpreting messages during communication. While spoken words carry explicit meaning, body language—including facial expressions, gestures, posture, eye contact, and proxemics (use of space)—provides a rich, often subconscious layer of information that significantly impacts how messages are received and understood. An understanding of body language is essential for effective communication, relationship building, and navigating social interactions, as it can reinforce, contradict, or even replace verbal communication. Studies suggest that nonverbal communication accounts for a significant portion of the total meaning conveyed in face-to-face interactions and Preserving Indigenous Languages.